Wired/wireless internet communications : 17th IFIP WG 6.2 International Conference, WWIC 2019, Bologna, Italy, June 17-18, 2019, Proceedings /: 17th IFIP WG 6.2 International Conference, WWIC 2019, Bologna, Italy, June 17-18, 2019, Proceedings. (2019) - Unknown
No abstract available